How to Conduct Effective Transnational Negotiations between Nations, Nongovernmental Organizations, and Business Firms - Charles B. Craver (Washington University Journal of Law & Policy, 2014)
As computers, the Internet, and efficient transportation systems have generated a truly global political and economic world, the extent of governmental and private transnational negotiating has significantly increased. International political entities—such as the United Nations and its affiliates and the World Trade Organization (WTO)—and regional political/economic groups—such as the European Union, the Group of Eight (G-8), the expanded Group of Twenty (G-20), and the North American Free Trade Zone—have increased the number of bilateral and multilateral governmental bargaining interactions. Nongovernmental organizations (NGOs) have become increasingly involved with issues that were previously addressed exclusively through governmental channels. The simultaneous growth of multinational business firms has similarly increased the frequency of private transnational business negotiations. This Article explores the different types of governmental and business transnational negotiations, focusing on official inter-government discussions, the involvement of seemingly private citizens in governmental interactions, and transnational business negotiations. This Article then considers the impact of cultural differences on transnational dealings between governments and private business entities and focuses on the way governmental and business firm negotiators must prepare for such bargaining encounters. Then, this Article talks about how parties should initiate transnational interactions through what is called the Preliminary Stage and covers value creation during the Information Stage. Next, this Article explores value claiming during the Distributive and Closing Stages and emphasizes the need for value maximizing during the Cooperative Stage. And finally, this Article explores cell phone and e-mail interactions.
Keywords: transnational negotiations; bilateral negotiations; multilateral negotiations; NGOs; non-governmental organizations; transnational business negotiations; cultural differences; transnational negotiation styles; low-context culture; high-context culture; transnational negotiation stages; negotiation stages; cellphone communication; email communication